Edukasi Bahan Tambahan Pangan yang Halal, Sehat dan Bergizi untuk Masyarakat Kelurahan Talaka - Santi Santi (Warta Pengabdian Andalas, 2023)
Food is one of the basic human needs, and food is usually given food additives. However, public knowledge about food additives still needs to be improved in terms of type, appropriate dosage for use and impact on human health. Apart from being good, food must also be halal, but public understanding of halal food ingredients and the contamination of non-halal ingredients into food is still lacking. This community service activity aims to increase public knowledge, especially in Talaka village, about food additives that are halal, healthy and nutritious and to be able to recognize products that contain food additives that are dangerous to health. This activity was carried out through introductions, giving pre-test questionnaires, providing education on halal, healthy and nutritious food, and giving a post-test afterwards. Nineteen participants answered questions correctly before education was 50%, while after education it was improved to 75%. Based on the results of observations and discussions with counselling participants, information was obtained that the public already understands the importance of choosing food products that are hygienic, halal, healthy and nutritious and that the public knows about additional ingredients—permitted and prohibited foods for food products.